DISKRESI PENAHANAN TERSANGKA DALAM PROSES PERADILAN PIDANA BERDASARKAN ASAS KEADILAN - Akbar, Achmad Asryel; Mardany, Alifian Fahdzan (Law Jurnal, 2023)
Detention of suspects is one of the instruments the criminal justice system uses to ensure the continuity of the legal process and maintain public order. In implementing the arrest of suspects, principles of justice are needed to ensure individual rights are protected. This legal research identifies the discretion of law enforcement officials in carrying out detentions and then analyzes aspects of justice. From the results of this research, it was concluded that detaining suspects involves complex elements of justice. The principles of justice, such as the presumption of innocence, proportionality, humanity and fair treatment, must be the basis for implementing the discretion to detain suspects. In this case, law enforcement must consider strong evidence and legitimate interests in detaining someone. Apart from that, it was revealed that there were challenges in implementing the discretion to detain suspects, including the tendency to abuse authority, inaccuracy in determining the period of detention, and low access to legal aid for less fortunate suspects. Based on these findings, this research recommends increasing the understanding and awareness of law enforcement officials regarding the importance of considering the principles of justice in implementing the discretion to detain suspects. As well as legal reform to strengthen the protection of suspects' rights, including stricter supervision of abuse of authority and increasing access to legal aid.